Применение информационной энтропии при описании нечетких множеств - Губаренко, Е. В. (ХНУРЭ, 2008)
In work the approach to the description of uncertainty of indistinct sets through information entropy is considered. Techniques on ambiguity elimination in interpretation of received results are offered.
Keywords: информационная энтропия